Pendampingan Pada Masyarakat di Kantor Imigrasi Kelas I TPI Denpasar tentang Perlindungan Status dan Hak Berkewarganegaraan Ganda - Ni Putu Febri Lintang Rahayu; Dewa Ayu Putu Adhiya Garini Putri (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
The state apparatus, namely immigration, has a very important role in resolving the problem of dual citizenship, with its authority to regulate and protect traffic and the safety of people related to the country. This study aims to analyze the role of the Class I Immigration Office of TPI Denpasar in carrying out its duties for the protection and fulfillment of rights to children with dual citizenship (ABG). The method used in the implementation of this activity is direct observation, and also assistance activities in providing information related to the requirements and procedures for registering children with dual citizenship. With the results of the discussion, the Class I Immigration Office of TPI Denpasar has played an important role in ensuring the fulfillment of rights and obligations as well as protection for the citizens, and also immigration carries out monitoring of dual citizenship children at the time of arrival and departure such as the right to temporarily stay in Indonesia or travel to other countries.